Fundamentals of nanoscale materials and technology - Siegel, Richard W. (Henry Stewart Talks, 2015)
Synthesis and characterization of nanostructured materials, Assembly of nanoscale building blocks into useful materials and devices, Nanocomposites and hierarchical material systems, Nanomedicine and nanotechnology for healthcare